Influence of Knowledge Management Practices on Entrepreneurial and Organizational Performance: A Mediated-Moderation Model - Li, Cai; Ashraf, Sheikh Farhan; Shahzad, Fakhar; Bashir, Iram; Murad, Majid; Syed, Nausheen; Riaz, Madiha (Frontiers in Psychology, 2020)
This study aims to identify the influence of knowledge management practices on the entrepreneurial 15 and organizational performance with the mediating effect of dynamic capabilities and moderating 16 role of opportunity recognition. Data were gathered from 486 entrepreneurs and applied a structural 17 equation model to test the hypotheses. We found that knowledge management practices have a 18 positive and significant influence on dynamic capabilities, as well as have a significant impact on 19 entrepreneurial and organizational performance. Moreover, results indicated that dynamic capabilities 20 partially mediate in the relationship between knowledge management practices on entrepreneurial 21 and organizational performance. Furthermore, the relationship between knowledge management 22 practices with entrepreneurial and organizational performance strengthening by opportunity 23 recognition. Further, implications and limitations were discussed in the paper.